فاعلية الإنفوجرافيك التفاعلي في تنمية مهارات التفكير البصري في مادة العلوم الحياتية لدى طلبة الصف العاشر في محافظة الخليل - فلسطين - التميمي، وليد نعيم بدوي الداعور; عودة، فادي (اتحاد الجامعات العربية - الأمانة العامة, 2023)
هدف المقال التعرف على أثر فاعلية الانفوجرافيك التفاعلي في تنمية مهارات التفكير البصري في مادة العلوم الحياتية لدى طلبة الصف العاشر في محافظة الخليل - فلسطين، ولتحقيق هدف الدراسة تم استخدام المنهج شبه التجريبي وتم اختيار عينة الدراسة التي تكونت من (50) طالبًا وطالبة من طلبة الصف العاشر من مدرستي الحسين بن علي الثانوية للبنين ومدرسة اسحق القواسمة الثانوية للبنات للفصل الدراسي الثاني من العام 2022/2021. ووزعت عينة الدراسة بالطريقة العشوائية إلى مجموعتين، التجريبية: وتكونت من (25) طالبًا وطالبة تم تدريسها مادة العلوم الحياتية باستخدام الانفوجرافيك التفاعلي، والمجموعة الضابطة وتكونت من (25) طالبًا وطالبة تم تدريسها مادة العلوم الحياتية بالطريقة الاعتيادية. ومن أجل تحقيق هدف الدراسة، تم إعداد أداتي الدراسة الاختبار التحصيلي، واختبار التفكير البصري (قبلي وبعدي) وتم التحقق من صدقهما وثباتهما. وأظهرت النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.05≥α) بين متوسطات درجات المجموعة الضابطة والمجموعة التجريبية، لصالح المجموعة التجريبية في الاختبار البعدي، والتي درست باستخدام الانفوجرافيك التفاعلي وقد كشفت الدراسة عن فاعلية الانفوجرافيك التفاعلي في تنمية التحصيل الدراسي وتنمية التفكير البصري لدى الطلبة. وفي ضوء النتائج أوصى الباحث باستخدام الانفوجرافيك التفاعلي في العملية التعليمية لما له من دور كبير في تنمية مهارات الطالب. The article aimed to identify the impact of the effectiveness of interactive infographics on developing visual thinking skills in the subject of life sciences among tenth-grade students in Hebron Governorate- Palestine. To achieve the objective of the study, the semi-experimental approach was used. The tenth grade of Al-Hussein Bin Ali Secondary School for Boys and Ishaq Al-Qawasmeh Secondary School for Girls for the second semester of the year 2021/2022. The sample of the study was randomly distributed into two groups, the experimental one: it consisted of (25) male and female students who were taught life sciences subject using interactive infographics, and the control group consisted of (25) male and female students who were taught life sciences subject in the usual way. In order to achieve the aim of the study, the two tools of the study, the achievement test, and the visual thinking test (pre and post), were prepared, and their validity and reliability were verified. The results showed that there were statistically significant differences at the level (a≤0.05) between the mean scores of the control group and the experimental group, in favor of the experimental group in the post-test, which was studied using interactive infographics. The study revealed the effectiveness of interactive infographics in developing academic achievement and developing visual thinking among students. In light of the results, the researcher recommended the use of interactive infographics in the educational process because of its great role in developing student skills.
Keywords: استراتيجيات التفكير -- التفكير المرئي -- تقنيات الفيديو -- المناهج الدراسية -- الإنفوجرافيك التعليمي